Ensino de geografia e o trabalho de campo: construindo possibilidades de ensino e aprendizagem sobre o espaço urbano e rural em Júlio de Castilhos, RS - Cioccari, Carmen Candida (2013)
The research is related to the use of instruments, methodologies and tools for learning the pedagogical practices of the discipline of geography. The problematic of this research is to analyze critically, in order to understand it, how the geography lessons are developed, in the context of learning in the public school.The problem derived from the following questions: What is the importance of field work for geography lessons? According to the inductive and deductive methods, what is the role of the field work in the composition of geographic knowledge? Does the participation and interaction of students, in a formative process, contribute to the development of the knowledge construction in geography lessons? The overall objective of this article is to evaluate the different perspectives used in the practice of field work as a guiding foundation of learning geography in elementary school. The methodology to be developed in this research focuses on field work present as a background in geographic education, since it has variables in learning activities, contextualized in environments that are not formal, where students will come in contact with objects and real situations, related to the daily life and, at the same time, with the scientificity of contents of proposed studies.The fieldwork was conducted in two environments and divided into two parts, the first part was developed in the urban environment using the deductive method and the second, in a rural setting with the use of the inductive method. The results obtained were different in the sense of knowledge construction, but both were successful.